USMKLE MEDICAL STUDENTS MADE THE NATION PROUD - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, January 2017 – Ten MARA sponsored medical students from the Universiti Sains MalaysiaKarnataka Lingayat Education (USMKLE) International Medical Programme have made the country proud when they emerged as champion in the ‘Battle of Fusion Band’ competition held in conjunction with the Umang Youth, International Kite Festival in Belgaum, India from 2124 January 2017.